A Study on Social Network Blogs as Business Tool on Information Technology Students' Perspective - Mohd Zairol, Yusoff (2010)
Blog has become an important element of popular culture, mass media and the daily lives. Despite the medium's interactive nature, most research on blog focus on the blog and blogger, rarely focusing on the user acceptance. In order to gain better understanding us of social practice of blogging we must take into account the acceptance, perception and credibility impact of the user. This research paper gives attention on blog acceptance as one of the business tools and its credibility for IT students in Universiti Utara Malaysia (UUM) Sintok, Kedah. Comprehensive on the market business information would be vital to the businesses. From this research, data and information from student perspective would very useful to the company especially to see student tendency use business blog because there are young people and have the influence factors to the community. This paper would look into deeper the correlation of the student's acceptance on to the business blog and what is the credibility impact to the students. The survey was done using the questionnaire consists of five section and twenty six questions. One hundred students from undergraduate and postgraduate students were selected in this study. About 80 percent questionnaires has been reply. Overall finding results show that students like to use blog but do not like to use business blog. Students have knowledge about business blog and believe most of the information on business blog is very important source to the people. This study also found that there are no significant different between undergraduate students and postgraduate students in term of acceptance, perception and belief towards business blog.